Pattern understanding: relationships with arithmetic and reading development - Burgoyne, K; Witteveen, K; Tolan, A; Malone, S; Hulme, C (Wiley, 2017)
Pattern understanding (patterning) is commonly taught in preschool and early elementary classrooms. However, the relationship between patterning and academic attainment is not well understood. In this article, we review studies of children's pattern understanding. Some evidence suggests that pattern understanding is related causally to acquiring math and reading skills. However, much of the evidence is weak and these conclusions remain tentative. Research on the relationship between patterning and other skills needs to use psychometrically robust measures and analytic techniques that control for the effects of measurement error. Recent studies suggest that teaching young children patterning skills can improve their attainment in math and reading, but we need larger, methodologically robust, randomized controlled trials to confirm such claims.